2017
DOI: 10.1039/c7cp05175a
|View full text |Cite
|
Sign up to set email alerts
|

Reply to the ‘Comment on “Elucidation of charge-transfer SERS selection rules by considering the excited state properties and the role of electrode potential”’ by M. Mohammadpour, M. H. Khodabandeh, L. Visscher and Z. Jamshidi, Phys. Chem. Chem. Phys., 2017, 19, 7833

Abstract: We appreciate Aranda's comments on our recent work entitled ''Elucidation of charge-transfer SERS selection rules by considering the excited state properties and the role of electrode potential''. We would also like to thank the editor of Physical Chemistry Chemical Physics for giving us an opportunity to specify more details of our work in this reply. An important part of our article concerns the role of the electrode potential in charge-transfer SERS spectra and we would like to first address the questions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…In continuation of our previous researches on the design and application of heterogeneous and reusable solid catalysts in organic synthesis and MCRs, [55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71] here we report an efficient and green method for the synthesis of 3,4-disubstituted isoxazole-5(4H)-ones catalyzed by HAp nanoparticles (Scheme 1).…”
Section: Resultsmentioning
confidence: 96%
“…In continuation of our previous researches on the design and application of heterogeneous and reusable solid catalysts in organic synthesis and MCRs, [55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71] here we report an efficient and green method for the synthesis of 3,4-disubstituted isoxazole-5(4H)-ones catalyzed by HAp nanoparticles (Scheme 1).…”
Section: Resultsmentioning
confidence: 96%
“…All the DFT calculations were completed using the Gaussian09 program package, 18,19 the structural analysis and data processing were conducted using the GaussView program, and all the geometric structure graphics were generated with the CYLview software. During the simulation, a Co 6 S 6 cluster was used to mimic the Co 1−x S cluster to make the calculation more affordable.…”
Section: Dft Calculations and Computational Methodsmentioning
confidence: 99%
“…The synthesis of 4H-pyrans 4 was achieved via a threecomponents condensation of aldehydes 1, malononitrile 2, and 1,3-diketone under reaction conditions (Methods A-H, Scheme 4, Table 1). [36][37][38][39][40][41][42][43] Maghsoodlou et al [44] and Mohamadpour et al [45] reported the synthesis of spiro 4H-pyran 7 and 8 by a three-component reaction of isatin 5 or acenaphthequinone 6 with malononitrile 2 and diketone 3 in different media (Methods A and B, Scheme 5).…”
Section: Synthesis Of 4h-pyransmentioning
confidence: 99%